Current Progresses in Metal-based Anticancer Complexes as Mammalian TrxR Inhibitors - Cheng, Yizhe; Qi, Yan (Anti-Cancer Agents in Medicinal Chemistry, 2017)
Reactive oxygen species (ROS) are produced as normal products of cellular metabolism, which are essential for numerous cell biological functions. Due to aberrant metabolism, oncogenic signaling activation and mitochondrial dysfunction, cancer cells generate excessive ROS that cause severe oxidative damage, finally leading to tumor cell death. Thioredoxin reductase (TrxR), as an important ROS-scavenging enzyme, is overexpressed in various human tumors and plays an important role in regulating intracellular redox homeostasis to protect cancer cells from cell death induced by substantial ROS. Hence, TrxR has emerged as a promising target for anticancer agent development. Currently, metallodrugs with anticancer activity, especially gold- and platinum-complexes, have an enormous impact on clinical cancer chemotherapy. This review provides a comprehensive overview of various metal complexes (gold, platinum, ruthenium, rhodium, iridium, iron, palladium, silver, antimony, bismuth, tin) targeting mammalian TrxR and discusses their cytotoxicity in tumor cells.
Keywords: platinum complexes